1991
DOI: 10.3382/ps.0700892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Extract on Nitrogen-Corrected True Metabolizable Energy for Soybean Meal with Broilers and Roosters

Abstract: Forty-day-old Arbor Acre x Ross male broilers were precision-fed 44% soybean meal (SBM) or 80%-etnanol extracted SBM (ESBM) to determine differences in TMEQ values due to the removal of oligosaccharides. The SBM had a dry matter crude protein content of 47.2% and the TMEn value of 2,546 kcal/kg. The ESBM had a dry matter crude protein content of 64.4% and TMEn value of 3,117 kcal/kg. In a second experiment, Leghorn roosters were precision-fed SBM, ESBM, ESBM containing 5.3% raffinose (RAF), or ESBM plus the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 6 publications
1
19
0
1
Order By: Relevance
“…Numerous articles have been published in recent years describing the negative influence of the oligosaccharides found in soyabean meal on the TME N value (Baker et al, 2011;Perryman et al, 2013). The deterioration of the TME N value in soyabean meal is attributed, primarily, to raffinose (Leske et al, 1991). The raffinose concentration in soyabean meal amounts to about 0.6% (Parsons et al, 2000), whereas in pea seeds it can be even as high as 1% (Zduńczyk et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles have been published in recent years describing the negative influence of the oligosaccharides found in soyabean meal on the TME N value (Baker et al, 2011;Perryman et al, 2013). The deterioration of the TME N value in soyabean meal is attributed, primarily, to raffinose (Leske et al, 1991). The raffinose concentration in soyabean meal amounts to about 0.6% (Parsons et al, 2000), whereas in pea seeds it can be even as high as 1% (Zduńczyk et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that stachyose and raffinose contents affect the AME N of soya protein concentrate and soyabean meal (SBM) (Coon et al, 1990;Leske et al, 1993). When SBM low in oligosaccharides was used in broiler chickens (Leske et al, 1991(Leske et al, , 1993Baker et al, 2011;Chen et al, 2013;Perryman et al, 2013), or SBM isolate in turkeys (Jankowski et al, 2009), better nutrient utilization and growth performance were observed. In agreement with the above results, the AME N of the investigated L. angustifolius seeds depended on the raffinose level (r 2 = 0.512; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Lupin seeds having the highest raffinose content (14.5 g · kg -1 ) were also characterized by the lowest AME N level (7.91 MJ · kg -1 , r = -0.72). As suggested by Leske et al (1991), high concentrations of these oligosaccharides in the digestive tract may cause water retention and, consequently, increase the digesta flow rate, leading to adverse effects on nutrient absorption and utilization and low AME. Generally, it is suggested that legume oligosaccharides have hygroscopic properties and may affect transit of gastrointestinal tract (GIT) digesta (Bedford, 1996) by elevating intestinal osmolarity (Smits and Annison, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the removal of the oligosaccharides in soybean meal by ethanol extraction increased the nitrogen corrected true metabolizable energy (TME n ) by 21% due to increased fiber digestion and the digesta passage rate was reduced by approximately 50%. Further studies by Coon and coworkers (Leske et al, 1991(Leske et al, , 1993) also demonstrated the improved TME n of soybean meal through alcohol extraction with both roosters and broilers. The recombination of the alcohol extract or addition of pure raffinose and stachyose to soy protein concentrate yielded TME n values that were similar to those of soybean meal.…”
Section: The Use Of Exogenous Enzymes To Increase the Nutritional Valmentioning
confidence: 99%